2010
DOI: 10.1001/archsurg.2009.208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Specialization on Emergency Colorectal Surgery Outcomes

Abstract: Specialization in colorectal surgery has a significant influence on morbidity, mortality, and anastomotic dehiscence after emergency operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 27 publications
(34 reference statements)
8
61
1
5
Order By: Relevance
“…18 It is interesting that these data suggest that 30-day mortality appeared significantly lower if emergency colonic resection is performed by subspecialist colorectal surgeons rather than non-colorectal specialists. Significantly better postoperative morbidity, 19,20 mortality, 20,21 stoma rate, 19,21 primary anastomosis rate 21 and anastomotic leak rate 20 have been reported previously for those emergency colorectal cases operated on by colorectal subspecialists. The unadjusted data from this study are best regarded as preliminary.…”
Section: Discussionmentioning
confidence: 52%
“…18 It is interesting that these data suggest that 30-day mortality appeared significantly lower if emergency colonic resection is performed by subspecialist colorectal surgeons rather than non-colorectal specialists. Significantly better postoperative morbidity, 19,20 mortality, 20,21 stoma rate, 19,21 primary anastomosis rate 21 and anastomotic leak rate 20 have been reported previously for those emergency colorectal cases operated on by colorectal subspecialists. The unadjusted data from this study are best regarded as preliminary.…”
Section: Discussionmentioning
confidence: 52%
“…The fact that there is less expertise available on weekends might be a substantial contributor to our findings. This is supported by Biondo et al 41 and Zorcolo et al, 42 who showed that experienced and specialized colorectal surgeons perform more primary anastomoses compared with trainees or general surgeons. The results of this population-based study provide strong evidence that postoperative adverse outcomes of urgent operations for left-sided diverticulitis are more frequent in patients admitted on weekends than in patients admitted on weekdays.…”
Section: Commentmentioning
confidence: 70%
“…Interestingly, until recently, nonelective colorectal surgery in the Netherlands was performed by almost all general surgeons on call, while other high-risk procedures, such as acute aneurysm surgery, are performed by specialized surgeons only. Previous studies have demonstrated that the presence of a specialized surgeon during a nonelective operation improves outcome [18,19]. Unfortunately, our database did not contain information on the qualifications of the operating surgeon, but it is likely that referral of high-risk nonelective patients to centers with a specialized surgeon available during on-call hours, improves outcome.…”
Section: Discussionmentioning
confidence: 99%